A ressurreição de Jesus Cristo : uma compreensão contemporânea - Duarte, Jonas da Silva (2021)
This dissertation is about a theoretical compilation research on the resurrection of Jesus Christ from the perspective of modernity and new cultural paradigms, aiming to present a possible understanding that is more compatible with contemporaneity. The foundations of faith in the resurrection conceived by the first Christians and the nascent Church until the middle of the third century d. C. are the source for the theme update. The research goes through the origins of the resurrection in the Old Testament and in some pagan peoples, passing through the thought of the apostolic fathers, apologists, the first great theologians, some of the important apocryphal gospels and the entire New Testament including the resurrection in Paul. Objectively, it seeks to understand what faith in the resurrection of Jesus Christ meant for the first Christians, and what does it mean today? What is the mode (or the “how”) of the resurrection? In short, how is the resurrection interpreted in such a way as to understand, at the present time, the same content, meaning and impact caused in the Early Church? Important theologians of the present time also contribute with valuable subsidies for a reliable updating of the theme. As for the mode of resurrection, it points to the transformation and glorification of the body described by Paul in the First Letter to the Corinthians. This transformation is deduced through the perspective of Quantum Physics, in perfect harmony with the apostle and the New Testament. As far as the meaning of the resurrection is concerned, it converges on a process and an eschatological question. It is perceived as the beginning of divine justification in the world, the inauguration of a 4 process of universal human conversion that involved repentance, together with a wonderful experience of forgiveness and grace provided by the Risen One. The resurrection of Jesus Christ was and is also conceived as the anticipation and cause of the awakening of the dead in and at the end of time.